2010
DOI: 10.1002/mrd.21171
|View full text |Cite
|
Sign up to set email alerts
|

Expression of zinc finger protein 105 in the testis and its role in male fertility

Abstract: Using an in silico approach, we identified a putative zinc finger domain-containing transcription factor (zinc finger protein 105, ZFP105) that was enriched in the adult mouse testis. RT-PCR analyses showed that Zfp105 was indeed highly expressed in adult mouse testis and that its expression was regulated during postnatal development. To further characterize Zfp105 expression, we generated a Zfp105:β-galactosidase (LacZ) knock-in reporter mouse line (Zfp105 LacZ/+ ) in which a Zfp105:LacZ fusion gene was expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Recently, studies demonstrated that several zinc finger proteins including ZNF230 (13), ZNF105 (14) and ZNF300 (15) were expressed specifically in testis and closely related to spermatogenesis and male reproduction. ZNF185 also belongs to the zinc finger protein family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies demonstrated that several zinc finger proteins including ZNF230 (13), ZNF105 (14) and ZNF300 (15) were expressed specifically in testis and closely related to spermatogenesis and male reproduction. ZNF185 also belongs to the zinc finger protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger protein is one kind of transcription factor, which is widely existed in organisms, and plays an important role in cell proliferation, cell differentiation and cell apoptosis (9)(10)(11)(12). At present, several studies demonstrated that zinc finger protein was expressed specifically in testis, such as ZNF230 (13), ZNF105 (14) and ZNF300 (15), and closely associated with spermatogenesis and male reproduction. ZNF185, also known as ZFP185, is belonging to the ZNF family and identified by Heiss for the first time in 1997 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc finger proteins (ZNFs) consist of a series of molecules that have important biological functions . Recently, several studies have reported different zinc finger proteins, including ZNF185, ZNF230, ZNF105, and ZNF300, as being involved in spermatogenesis and male reproduction . Notably, ZNF185 belongs to the ZNF family and was identified by Heiss in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recently, several studies have reported different zinc finger proteins, including ZNF185, ZNF230, ZNF105, and ZNF300, as being involved in spermatogenesis and male reproduction. [8][9][10][11] Notably, ZNF185 belongs to the ZNF family and was identified by Heiss in 1997. It is located on the DXS52 region of Shutong Fan and Yuhan Zhao are co-first authors.…”
mentioning
confidence: 99%
“…Several Cys2/His2 zinc finger proteins are also expressed at specific stages during mouse spermatogenesis. For example, deficiency of ZFP105 in pachytene spermatocytes resulted in undifferentiated spermatogenic cells and decreased male fertility (Zhou et al 2010). Ovol2/MOVO may play an important role in the XY body during spermatogenesis, possibly in XY body formation and meiotic sex chromosome inactivation (Chizaki et al 2012).…”
Section: Introductionmentioning
confidence: 99%